2022
DOI: 10.3389/fdmed.2022.826387
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on Dentoalveolar Manifestations Resulting From PHOSPHO1 Loss-of-Function: A Form of Pseudohypophosphatasia?

Abstract: Mineralization of the skeleton occurs by several physicochemical and biochemical processes and mechanisms that facilitate the deposition of hydroxyapatite (HA) in specific areas of the extracellular matrix (ECM). Two key phosphatases, phosphatase, orphan 1 (PHOSPHO1) and tissue-non-specific alkaline phosphatase (TNAP), play complementary roles in the mineralization process. The actions of PHOSPHO1 on phosphocholine and phosphoethanolamine in matrix vesicles (MVs) produce inorganic phosphate (Pi) for the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…(19,68) Given that the symptomatology of Phospho1 À/À mice resembles many of the manifestations of HPP, we surmised that Phos-pho1 gene mutations could be associated with cases of pseudo-HPP, where TNAP may be normal to subnormal, but an ALPL mutation has not been identified. (11) Overexpressing TNAP under control of the ApoE promoter, in the Phospho1 À/À mice did not prevent the skeletal defect in that model but ablating Spp1 (osteopontin [OPN]) in the Phospho1 À/À mice helped improve the skeletal phenotype. (69) We concluded that although Alpl and Phospho1 deficiencies lead to similar skeletal phenotypes and a parallel increase in the plasma levels of PP i and OPN, there was an apparent dissociation in the hierarchical roles of these potent inhibitors of mineralization, with elevated PP i and elevated OPN levels causing the respective skeletal phenotypes in Alpl À/À and Phospho1 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(19,68) Given that the symptomatology of Phospho1 À/À mice resembles many of the manifestations of HPP, we surmised that Phos-pho1 gene mutations could be associated with cases of pseudo-HPP, where TNAP may be normal to subnormal, but an ALPL mutation has not been identified. (11) Overexpressing TNAP under control of the ApoE promoter, in the Phospho1 À/À mice did not prevent the skeletal defect in that model but ablating Spp1 (osteopontin [OPN]) in the Phospho1 À/À mice helped improve the skeletal phenotype. (69) We concluded that although Alpl and Phospho1 deficiencies lead to similar skeletal phenotypes and a parallel increase in the plasma levels of PP i and OPN, there was an apparent dissociation in the hierarchical roles of these potent inhibitors of mineralization, with elevated PP i and elevated OPN levels causing the respective skeletal phenotypes in Alpl À/À and Phospho1 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that, indeed, the use of AAV8‐TNAP‐D 10 prevents severe scoliosis that characterizes this murine model with improvements in the trabecular bone and a reduced marrow space in the vertebrae of AAV8‐TNAP‐D 10 ‐treated Phospho1 −/− mice. In a recent perspective, ( 11 ) we discussed that Phospho1 gene mutations may underlie some cases of “pseudo‐HPP,” where ALP may be normal to subnormal, but ALPL mutation(s) have not been identified. These patients would be expected to have skeletal defects such as osteomalacia and fractures consistent with HPP but featuring dental phenotypes with mild enamel and dentin effects and intact cementum, periodontal attachment, and no premature tooth loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations